The two-family house - Loigman, Lynda Cohen (St. Martin's Press, 2016)
"Brooklyn, 1947: in the midst of a blizzard, in a two-family brownstone, two babies are born minutes apart to two women. They are sisters by marriage with an impenetrable bond forged before and during that dramatic night; but as the years progress, small cracks start to appear and their once deep friendship begins to unravel. No one knows why, and no one can stop it. One misguided choice; one moment of tragedy. Heartbreak wars with happiness and almost but not quite wins.From debut novelist Lynda Cohen Loigman comes The Two-Family House, a moving family saga filled with heart, emotion, longing, love, and mystery. "Two families, both living in one house, drive an exquisitely written novel of love, alliances, the messiness of life and long buried secrets. Loigman's debut is just shatteringly wonderful and I can't wait to see what she does next." - Caroline Leavitt, New York Times bestselling author of Is This Tomorrow and Pictures of You"No good deed goes unpunished. In a single, intensely charged moment, two women come to a private agreement meant to assure each other's happiness. But as Lynda Cohen Loigman deftly reveals, life is not so simple, especially when it involves two families, tightly intertwined. The Two-Family House is sympathetically observed and surely plotted all the way through to its deeply satisfying conclusion." - Christina Schwarz, author of Drowning Ruth (an Oprah's Book Club pick) and national bestseller The Edge of the Earth"--